2017
DOI: 10.1016/j.jfca.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic, sugar and acid profiles and the antioxidant composition in the peel and pulp of peach fruits

Abstract: In this study, antioxidant compounds (ascorbic acid; total phenolic, flavonoid and anthocyanin contents; and relative antioxidant capacity) and the profiles of sugars, organic acids, polyphenols and mineral composition were compared in the peel and pulp tissues of nine commercial peach cultivars. The antioxidant compounds, measured by a 96-well-microplate-reader, showed differences among cultivars. The phenolic profile determined by UPLC resulted in the quantification of hydroxycinnamates, flavonols (only in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
75
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 36 publications
(32 reference statements)
19
75
1
3
Order By: Relevance
“…The peel extract contents of total phenolic and flavonoids were higher than the flesh extract of C. tuberosus. The results were in agreement with the research conducted by Ahmadi-Alfazi et al (2015) and Saidani et al (2017). Total phenolics compounds acres fills up in higher amounts extracted with a more polar solvent.…”
Section: Levels Of Phytochemicalssupporting
confidence: 92%
“…The peel extract contents of total phenolic and flavonoids were higher than the flesh extract of C. tuberosus. The results were in agreement with the research conducted by Ahmadi-Alfazi et al (2015) and Saidani et al (2017). Total phenolics compounds acres fills up in higher amounts extracted with a more polar solvent.…”
Section: Levels Of Phytochemicalssupporting
confidence: 92%
“…The maintenance of the prebiotic content indicate that the probiotic cultures did not use oligofructose in the metabolism and the prebi- The antioxidant activity was similar those reported in previous studies (Hmid et al, 2017;Saidani et al, 2017). Therefore, the orange juice and hibiscus tea mixed beverages presented TPC contents similar to other juices recognized for their high content of phenolic compounds, which contributed to the high antioxidant activities observed.…”
Section: Oligofructose Content Bioactive Compounds and Antioxidansupporting
confidence: 83%
“…The TPC content was in the range observed in orange juice (607.9 mg EAG L −1 , Table ), peach juice (400–1,620 mg EAG L −1 ; Saidani et al, ), apple juice (200–600 mg EAG L −1 , Persic, Mikulic‐Petkovsek, Slatnar, & Veberic, ), grape juice (500 mg EAG L −1 , Quan et al, ), and pomelo juice (500 mg EAG L −1 , Quan et al, ), but lower than those observed in pomegranate juice (1,385–9,476 mg EAG L −1 , Hmid, Elothmani, Hanine, Oukabli, & Mehinagic, ) and kiwi juice (1,000 mg EAG L −1 , Quan et al, ). The antioxidant activity was similar those reported in previous studies (Hmid et al, ; Saidani et al, ). Therefore, the orange juice and hibiscus tea mixed beverages presented TPC contents similar to other juices recognized for their high content of phenolic compounds, which contributed to the high antioxidant activities observed.…”
Section: Resultsmentioning
confidence: 80%
“…Plants have the innate ability to synthesize, constitutively or in response to abiotic and biotic stress conditions, non‐enzymatic antioxidants including secondary metabolites such as phenolic compounds, tannins, and anthocyanins. Likewise, some authors have found a significant correlation between antioxidant capacity, total phenols, and anthocyanins in different types of fruit . However, there have been variations in this response depending on the cultivar and the maturity state of fruit .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, some authors have found a significant correlation between antioxidant capacity, total phenols, and anthocyanins in different types of fruit. 4,5 However, there have been variations in this response depending on 6860 www.soci.org I Romero et al…”
Section: Introductionmentioning
confidence: 99%